2012
DOI: 10.5688/ajpe76223
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Education and Competency Development of Croatian Community Pharmacists Using the General Level Framework

Abstract: Objectives. To measure Croatian community pharmacists' progress in competency development using the General Level Framework (GLF) as an educational tool in a longitudinal study. Methods. Patient care competencies of 100 community pharmacists were evaluated twice, in 2009 and in 2010 in a prospective cohort study. During this 12-month period, tailored educational programs based on the GLF were organized and conducted, new services and standard operating procedures were implemented, and documentation of contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 16 publications
4
71
0
2
Order By: Relevance
“…27,28 Decision-making within strict time-constraints is common for community pharmacists. 3,13,14,21,23 Participant developmental phase changed for 12 (44%) of the participants during engagement with the educational intervention (Figure 3). The impact of the intervention concluded that the proportion of G1 participants in transition post-intervention increased to 75%, whereas the proportion of G2 participants in transition post-intervention decreased to 27% (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 Decision-making within strict time-constraints is common for community pharmacists. 3,13,14,21,23 Participant developmental phase changed for 12 (44%) of the participants during engagement with the educational intervention (Figure 3). The impact of the intervention concluded that the proportion of G1 participants in transition post-intervention increased to 75%, whereas the proportion of G2 participants in transition post-intervention decreased to 27% (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…19,20,21 Recent research highlight many potential sources of dilemmas, both personal to and external to pharmacists. 13,14,[21][22][23][24][25] The avoidance of professional dilemmas is therefore not possible for community pharmacists and decision-making through dilemma scenarios is likely to take place within strict time constraints and without direct access to pharmacist peers. 3,13,14,23 The DIT2 measures whether deeper level "bedrock" schemas are activated (to the extent that the person has developed them) and engaged when decision-making through dilemmas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition was chosen on the basis that it has been included in the updated EPOC taxonomy [36] and also been used in two similar reviews with a similar scope, but in different practice settings [1,16]. In the application of this definition, it was acknowledged that some studies would be excluded, for example, studies that looked at the implementation of practice standards that did not include guidance on clinical activities [39,40] and articles that looked at policy documents and frameworks [41,42]. One of the key determinations from the definition was that the guidelines needed to relate to "specific clinical circumstances."…”
Section: Interventionsmentioning
confidence: 99%
“…35 Recent research highlights many potential sources of dilemmas, both personal to and external to pharmacists. 13,14,34,[36][37][38][39] The avoidance of professional dilemmas is therefore not possible for community pharmacists 3,13,14,37 and decision-making through dilemma scenarios is likely to take place within strict time constraints and without direct access to pharmacist peers. 33,37 Despite perceived limitations with respect to the representativeness of volunteers for whom there was no remuneration or specific academic credit, and the expectation that attrition rates were likely to be high, 34,40,41 the volunteers nevertheless provide a snapshot of the population (of community pharmacists working in Ireland) at a particular point in time.…”
Section: Implementing Icms In Mrcd: An Examplementioning
confidence: 99%